Designing Digital Governance for International Nuclear Cooperation Using Soft Systems Methodology - Desiani Desiani; Alih Aji Nugroho; Dimas Irawan; Diah Triastuti; Nur Hasanah (Jurnal Publikasi Ilmu Manajemen, 2026)
This study aims to design a digital governance model to support international nuclear cooperation at the INuA Indonesia Secretariat, particularly in strengthening documentation, coordination, data management, and evidence-based decision-making. The study employs a qualitative approach using Soft Systems Methodology through the mapping of problematic situations, identification of actors, formulation of transformation needs, development of a conceptual model, and thematic analysis of data obtained from interviews, discussions, observations, and institutional documents. The findings indicate that the main need of the INuA Secretariat is not merely the development of a digital application, but the establishment of a socio-technical governance framework that integrates document repositories, activity databases, metadata standardization, role distribution, access control, follow-up tracking, automated reminders, and information dashboards. The implication of this study highlights the importance of gradual digital governance implementation to preserve institutional memory, improve coordination efficiency, strengthen to documentation accountability, and support sustainable decision-making in of international nuclear cooperation.